"If you stop playing you get old": investigating reflections of play in older adults. Issue 5 (4th May 2019) - Burr, Brandon; Atkins, Ladonna; Bertram, Anita Glee; Sears, Kaye; McGinnis, Andreae N.
ABSTRACT: Research shows various benefits of play in terms of children's development. However, very little investigation has explored play from a lifespan perspective, linking early play experiences to older adulthood. Although some prior research has explored play memories, very little information is available on play memories of older adults, specifically, and perceptions of the importance of play in older adults. Using a lifespan perspective, this study explored the phenomenon of play through stories and memories from interviews with 15 older adults. Major study themes highlight changes between past and present play activity. Implications for practitioners and researchers are presented.